2010
DOI: 10.1007/s10653-010-9319-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of drinking water, raw rice and cooking of rice as arsenic exposure routes in three contrasting areas of West Bengal, India

Abstract: Remediation aimed at reducing human exposure to groundwater arsenic in West Bengal, one of the regions most impacted by this environmental hazard, are currently largely focussed on reducing arsenic in drinking water. Rice and cooking of rice, however, have also been identified as important or potentially important exposure routes. Quantifying the relative importance of these exposure routes is critically required to inform the prioritisation and selection of remediation strategies. The aim of our study, theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
74
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(83 citation statements)
references
References 42 publications
7
74
1
1
Order By: Relevance
“…Groundwater that contains As concentrations >10 μg/L limit set by the World Health Organization (WHO) places more than ten million people at risk from arsenicosis. Locales ranging from Southern Bangladesh, India, Argentina, Chile, and Vietnam have groundwater sources with As concentrations >10 μg/L [2,3,6,25,26,[28][29][30][31][32][33].…”
Section: Arsenic Chemistry Geochemistry Prevalence and Toxicitymentioning
confidence: 99%
“…Groundwater that contains As concentrations >10 μg/L limit set by the World Health Organization (WHO) places more than ten million people at risk from arsenicosis. Locales ranging from Southern Bangladesh, India, Argentina, Chile, and Vietnam have groundwater sources with As concentrations >10 μg/L [2,3,6,25,26,[28][29][30][31][32][33].…”
Section: Arsenic Chemistry Geochemistry Prevalence and Toxicitymentioning
confidence: 99%
“…The principal exposures routes for As are via drinking water, foods and inhaled particulates (Mondal et al, 2010), with many studies detailing the importance of the food pathway to overall As body burdens (Georgopoulos et al, 2007;Meacher et al, 2002;Mondal et al, 2010;Schoof et al, 1999;Xue et al, 2010). In West Bengal (India) it has been shown that even for populations exposed to high As levels in the drinking water, rice constitutes a major source of iAs in the diet (Mondal and Polya, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In each incubation cycle we included a negative control consisting of sterile water, processed in the same way as the samples. We analyzed water samples for total arsenic by inductively coupled plasma mass spectrometry (ICP-MS) (Agilent 7500 Series ICP-MS) at the University of Manchester following the method outlined by Mondal et al [14].…”
Section: Sample Collection and Analysismentioning
confidence: 99%
“…The area selected for this study, Chakdha Block of Nadia District, West Bengal fulfils the requirements of being (i) geographically focused; (ii) an arsenic impacted area [1,13,14]; (iii) the site of several different arsenic mitigation strategies [15]; (iv) well studied with background information available [14][15][16] and (v) straightforward logistically. We calculated disability adjusted life years (DALYs) as a mean of comparing disease burden arising from the two water-borne hazards: arsenic and pathogens.…”
Section: Introductionmentioning
confidence: 99%